The EFFECT OF PARENTS' SUPPORT WITH ANXIETY LEVELS OF MENARCHE IN ADOLESCENT WOMEN AT SDN MURTAJIH 1 PADEMAWU, PAMEKASAN - Layla Imroatu Zulaikha; Sarindani Oktarina; Tri Yunita Fitria Damayanti (Universitas Islam Madura, 2023)
Menarchea is the first bleeding from the uterus that occurs in a woman. Menarche usually occurs at the age of 10-16 years, the average is 12.5 years. Many adolescents feel anxious when they are about to face menarche which is marked by shame and fear, with varying levels of anxiety. Based on the preliminary study, it was found that 60% of the young women did not get support from their parents, especially informative support regarding menstruation. The purpose of this study was to determine the relationship between parental support and the level of anxiety facing menarche in female adolescents. This research is a correlational analytic study with a cross sectional approach. The population is all students of the Murtajih 1 Elementary School. The sampling technique is random sampling of 71 respondents. Collecting data in this study using questionnaires and checklists. The data analysis technique used the Spearman rank statistical test with the help of SPSS version 17.0 with a significance level of 0.05. From the results of the Spearman rank statistical test, it was found that ρ : 0.000 <0.05, which means that H0 is rejected, which means that there is a relationship between parental support and the level of anxiety facing menarche in young women. Parental support is an important element in shaping perceptions in adolescents. Good parental support will help reduce the level of anxiety facing menarche in young women. Because that way, young women get information, especially about menstruation, which will give a positive perception about menarche. This requires awareness of parents as the first and foremost educators for their children.